Factors affecting employee creativity in Islamic banking in Pakistan - Andleeb, Naima (2021)
Islamic banking emerged as a response to both religious and economic needs in Islamic countries. Previous literature highlighted the need for more studies to focus employee creativity on staying competitive in this challenging market. Therefore, previous studies failed to discuss thoroughly cultural, behavioral, and internal factors affecting employee creativity, especially in Islamic banking. The current study integrated a framework on the factors affecting employee creativity suggested by practitioners and previous literature. This study's framework includes organizational culture with its nine dimensions, internal marketing, and employee creativity with the mediating effect of knowledge sharing. This study has seven main hypotheses to meet these objectives, and 15 hypotheses were tailored in total, including sub-hypothesis. A quantitative method was followed, and data were collected from a survey questionnaire from Islamic banks in Pakistan. The data analysis was conducted using Smart PLS 3.2.7 for 393 final clean respondents. The results show that both organizational culture and internal marketing have a positive effect on employee creativity jointly. However, three of the dimensions of organizational culture are not significant to employee creativity. Simultaneously power distance and performance orientation don’t support knowledge sharing in Islamic banking. Moreover, knowledge sharing is found as a significantly supported mediator. This study provides some implications for theory advancements and practical applications that can help practitioners better understand the issues related to organizational culture, internal marketing, employee creativity, and knowledge sharing in Pakistan's Islamic banking.